2021
DOI: 10.1038/s41598-021-97040-w
|View full text |Cite
|
Sign up to set email alerts
|

TRPA1 triggers hyperalgesia and inflammation after tooth bleaching

Abstract: Hyperalgesia has become a major problem restricting the clinical application of tooth bleaching. We hypothesized that transient receptor potential ankyrin 1 (TRPA1), a pain conduction tunnel, plays a role in tooth hyperalgesia and inflammation after bleaching. Dental pulp stem cells were seeded on the dentin side of the disc, which was cut from the premolar buccal tissue, with 15% (90 min) or 40% (3 × 15 min) bleaching gel applied on the enamel side, and treated with or without a TRPA1 inhibitor. The bleaching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…They activate TRPA1 expressed by neurons, which induces the release of SP and CGRP associated with neurogenic inflammation and a prolonged mechanical and thermal hypersensitivity state. More specifically, Chen et al (12) observed in pulp stem cells treated with a 15% hydrogen peroxide gel for 90 min or 40% for 45 min inducing oxidative stress and ROS production, an increase in the expression of TRPA1, intracellular absorption of Ca2+, activation of PANX1 favoring the secretion of ATP and its action as a neurotransmitter. In addition, TRPA1 upregulated TNF-ß and IL-6, inducing inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…They activate TRPA1 expressed by neurons, which induces the release of SP and CGRP associated with neurogenic inflammation and a prolonged mechanical and thermal hypersensitivity state. More specifically, Chen et al (12) observed in pulp stem cells treated with a 15% hydrogen peroxide gel for 90 min or 40% for 45 min inducing oxidative stress and ROS production, an increase in the expression of TRPA1, intracellular absorption of Ca2+, activation of PANX1 favoring the secretion of ATP and its action as a neurotransmitter. In addition, TRPA1 upregulated TNF-ß and IL-6, inducing inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in extracellular ATP levels in the cells suggested the possibility of TRPA1 activation by ROS stimulation. Others demonstrated that TRPA1 antagonist HC-030031 suppressed H 2 O 2 production-induced intracellular ROS, ATP release, and the mRNA and protein levels of PANX1 32 . These finding suggest that ATP is released via PANX1 in response to TRPA1 channel activation by the H 2 O 2 -induced ROS stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in rat incisor models of tooth bleaching have suggested that strong oxidative stress following treatment with high-dose H 2 O 2 induced ROS-mediated cytotoxicity in DPSCs, which could affect the hyperalgesia of tooth by regulating TRPA1 expression, intracellular Ca 2 + concentration, and ATP release into the extracellular space 32 , 34 . Moreover, oxidative stress in the periodontal tissue and dental pulp following orthodontic force is suggested to activate and/or mechanically sensitize TRPA1 on nociceptive fibers, resulting in orthodontic nociception 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Activation of TRPA1 promotes intracellular calcium uptake, increases adenosine triphosphate (ATP) secretion, and induces inflammatory pain, whilst also upregulating the expression of TNFα and IL-6. 79 Therefore, the interaction between TRPA1 and TNFα collectively participates in the inflammatory response of psoriasis.…”
Section: Sensory Neurons and Trp Family In Psoriasismentioning
confidence: 99%